2015
DOI: 10.1002/adfm.201404402
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Generation of Nitric Oxide by Near‐Infrared‐Sensitized Upconversion Nanoparticles for Tumor Therapy

Abstract: NaYbF4:Tm@NaYF4:Yb/Er upconversion nanoparticles are synthesized and then integrated with light‐sensitive nitric oxide (NO) donors (Roussin's black salt) to construct a novel near‐infrared (NIR)‐triggered on‐demand NO delivery platform. This nanocompound can absorb 980 nm NIR photons, convert them into higher energy photons and then transfer the energy to the NO donors, resulting in an efficient release of NO. By manipulating the output power of the 980‐nm NIR light, NO‐concentration‐dependent biological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
141
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 54 publications
1
141
0
3
Order By: Relevance
“…used a core-shell structure of UCNP@MSN as carrier of RBS to develop a NIR-responsive nanomedicine (UCNP@MSN-RBS) for NO controlled release. 6a,b How, the saturated RBS loading capacity of UCNP@MSN was merely 10wt%. In comparison, the developed sandwich structure of GO-BNN6 in this work has a remarkably higher drug loading capacity (120wt%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…used a core-shell structure of UCNP@MSN as carrier of RBS to develop a NIR-responsive nanomedicine (UCNP@MSN-RBS) for NO controlled release. 6a,b How, the saturated RBS loading capacity of UCNP@MSN was merely 10wt%. In comparison, the developed sandwich structure of GO-BNN6 in this work has a remarkably higher drug loading capacity (120wt%).…”
Section: Resultsmentioning
confidence: 99%
“…6a,b By comparison of their absorption spectra (Fig. 4A), it can be found that GO has a broad absorption band centered in the UV region, while GNR@MSN has a relatively narrow adsorption band centered in the NIR region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UCNPs have been successfully designed as a NIR sensitized system for NO carrying and therapy. [134][135][136] In these studies, Roussin's black salt (RBS) was used as the NO yielding source. UCNPs coated with SiO 2 /-NH 3þ , poly (dimethylsiloxane) composites, mSiO 2 were used for RBS carrying and photo-triggered releasing for cancer therapy.…”
Section: Ucnps For Chemotherapymentioning
confidence: 99%